Features of the work of a choreographer in the modern space: challenges and prospects - Omelchenko, A.; Arendt, N. (ХДАК, 2023)
Since the end of the XX century, significant interest has risen in ballroom dancing and its general popularization around the world. More and more people of all ages are coming to the social, ballroom, and Latin American dance, with a significant number of them entering the professional path. Only in Kyiv, since 1991, the year when Ukraine gained independence, more than 160 schools, studios and clubs have been opened; ballroom dance specializations and departments are being created in sports and artistic universities. The number of cities, where all-Ukrainian and even international competitions are held several times a month during the training season, is increasing.
Keywords: хореографія; бальні танці; choreography